Analisis Faktor-faktor yang Mempengaruhi Integritas Akademik Mahasiswa Keperawatan - Kabak, Edison (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study was to determine the factors that influence the academic integrity of Nursing students of the Health Polytechnic Health Polytechnic of Jayapura. In this research, the writer uses quantitative descriptive method. The population as well as the sample in this study were all students of the Nursing Education Program, totaling 176 students from semesters I, III and V. The method of analysis used was multiple regression analysis. The results showed; (1) The average score of 176 respondents on academic integrity is 3.64. This means that the academic integrity of Wamena Nursing Study Program students is high. (2) The average value of respondents on external factors is 3.95. This means that the student's external factors are classified as high (3) The average value of the respondents on internal factors is 4.34. This means that the student's internal factors are classified as Very High (4) External factors have a significant effect on academic integrity as evidenced by the value of Sig = 0.000 <0.05. Internal factors also have a significant effect on academic integrity as indicated by the value of Sig = 0.000 <0.05. Conclusions, external and internal factors have a significant effect on the academic integrity of Nursing students in the Health Polytechnic Nursing Education Program at the Ministry of Health in Jayapura. Keywords: internal factors, external factors, academic integrity